2020
DOI: 10.3390/ijerph17217973
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Selected Studies on the Factors Associated with the Nutrition Status of Children Under the Age of Five Years in South Africa

Abstract: Malnutrition is a considerable contributor to child mortality and morbidity. Child malnutrition further affects the country’s economic development. Child malnutrition in South Africa is persistent, continuing to be an alarming burden. The nutritional status of kids under the age of five years is a critical indicator of the country’s economic condition and health status. An understanding of the influencers of the nutritional status of children can act as a catalyst in combatting all forms of malnutrition. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0
9

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 103 publications
3
54
0
9
Order By: Relevance
“…The information from this analysis is in line with previous research in South Africa and Pakistan (Mahmood et al, 2020;Mkhize and Sibanda, 2020). Lack of sanitation facilities is also informed as a determinant of the stunted toddler (Mahmood et al, 2020).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The information from this analysis is in line with previous research in South Africa and Pakistan (Mahmood et al, 2020;Mkhize and Sibanda, 2020). Lack of sanitation facilities is also informed as a determinant of the stunted toddler (Mahmood et al, 2020).…”
Section: Resultssupporting
confidence: 83%
“…The study was conducted by reviewing 27 articles between 2010-2019 that reported on the factors influencing the nutritional status of children under the age of five years. The results of the review show that poor access to water is one of the determinants of stunted toddlers (Mkhize and Sibanda, 2020). Otherwise, previous studies in Indonesia, on a smaller scale, found different information.…”
Section: Resultsmentioning
confidence: 81%
“…The study was conducted by reviewing 27 articles between 2010-2019 that reported on the factors in uencing the nutritional status of children under the age of ve years. The results of the review show that poor access to water is one of the determinants of stunted toddlers (Mkhize and Sibanda, 2020). Otherwise, previous studies in Indonesia, on a smaller scale, found different information.…”
Section: Resultsmentioning
confidence: 81%
“…On the other hand, environmental factors were also found to be closely related to the incidence of stunting. It is informed that the availability of proper drinking water and environmental sanitation play a role as a determinant of stunting (Mkhize and Sibanda, 2020). Meanwhile, poverty and poor education cannot be separated as the dominant characteristics of households that have stunted toddlers (Buisman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 45% of deaths among children under 5 years of age can be attributed to undernutrition [ 6 ]. Childhood undernutrition may result in long-term effects that are irreversible, including impaired physical growth and cognitive development [ 7 , 8 , 9 ]. Furthermore, undernutrition may reduce sensory-motor abilities, reproductive function and increase children’s vulnerability to infections and hereditary diseases, such as diabetes [ 9 , 10 ].…”
mentioning
confidence: 99%